2018
DOI: 10.1186/s12858-018-0100-1
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of cysteine protease from miswak Salvadora persica

Abstract: BackgroundGenerally, proteases in medicinal plants had different therapeutic effects such as anti-inflammatory effect; modulate the immune response and inhibitory effect toward tumor growth. In this study, protease was purified and characterized from miswak roots, as medicinal plant and natural toothbrush.ResultsPhysical and chemical characterization of cysteine protease P1 were studied such as pH optimum (6.5), optimum temperature (50 °C), thermal stability (50 °C) and Km (3.3 mg azocasein/ml). The enzyme dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Concurrently, the variation in absorbance was recorded at a wavelength of 240 nm. A suspension was formulated containing 50 mM of potassium dihydrogen phosphate buffer, 120 mM of Met, 0.1 mM of EDTA, 700 µM of NBT, 60 µM of riboflavin, and 0.2 mL of enzyme extract, which was then used for the assessment of superoxide dismutase (SOD) activity [73].…”
Section: Determination Of Physiological and Biochemical Activitiesmentioning
confidence: 99%
“…Concurrently, the variation in absorbance was recorded at a wavelength of 240 nm. A suspension was formulated containing 50 mM of potassium dihydrogen phosphate buffer, 120 mM of Met, 0.1 mM of EDTA, 700 µM of NBT, 60 µM of riboflavin, and 0.2 mL of enzyme extract, which was then used for the assessment of superoxide dismutase (SOD) activity [73].…”
Section: Determination Of Physiological and Biochemical Activitiesmentioning
confidence: 99%
“…It was noted from the above-reported results as depicted in figure 9 that cotton seed protease prefers hydrolyzed peptones rather than other proteins. However, our finding is in variance with the reports of other researchers who investigated the substrate specificity of protease isolated from different plants such as cysteine protease from the fruit of Babi Kiwi exhibited high activity toward the synthetic substrate ZLeu-Arg-MCA and moderate activity toward Z-Val-Leu-LysMCA, Z-Val-Val-Arg-MCA, Z-Phe-Arg-MCA and Pro-PheArg-MCA, protease from miswak roots (Abdulaal, 2018)showed that the enzyme acted on casein, hemoglobin, egg albumin, gelatin and bovine serum albumin, three proteases from citrus sinensis fruit peel prefer to hydrolyzed gelatin than casein and bovine serum albumin and protease from seeds of Citrulluscolocynthis identified significantly high rates of hydrolysis for natural proteins such as hemoglobin, casein, gelatin and bovine serum albumin compared to modified proteins such as azoalbumin and azocasein (Khan, Khan, Shah, & Khan, 2016) .…”
Section: Figure 6 Effect Of Temperature On Purified Protease Activity...mentioning
confidence: 99%
“…The superoxide dismutase (SOD) activity was analyzed in 3 mL reaction mixture (50 mM potassium phosphate buffer (pH 7.0), 130mM Met, 0.1 mM EDTA, 750 µM NBT, 60 µM riboflavin and 0.2 mL of enzyme extract). One unit of SOD activity was defined as the quantity of enzyme required to induce 50% inhibition of the NBT reduction measured at 560 nm [52]. The ascorbate peroxidase (AXP) activity was analyzed in a 3 mL reaction mixture containing 50 mM potassium phosphate buffer (pH 7.0), 0.5 mM ASA, 6 mM H 2 O 2 and 50 µL of enzyme extract, and the changes in the absorbance at 290 nm were measured over a period of 30 s [53].…”
Section: Determination Of Physiological and Biochemical Activitiesmentioning
confidence: 99%